Upaya Meningkatkan Hasil Belajar PKn Materi Pokok Pancasila sebagai Ideologi Negara melalui Metode Diskusi Kelompok - Mega, Surya (Universitas Pendidikan Ganesha, 2018)
Based on the results of observations, interviews and evaluation results of the implementation of Civics subject learning stated by the class XII Semester 1 teacher and student of SMK Negeri 60 Jakarta, the 2015/2016 academic year obtained data that the implementation of Civic Education learning in SMK Negeri 60 Jakarta still requires innovation from various aspects in accordance with PKn subject learning material. Pre-cycle results conducted by the researchers at the beginning of this study were low or below the KKM, which was 61.43 with the percentage of success in learning reaching 46.66%. Seeing such conditions Researchers are encouraged to make improvements through Classroom Action Research by applying group discussion learning methods where the application of group discussion learning methods is believed to be able to improve student learning outcomes to a level better. The main objectives in this study are: to find out the improvement of student learning outcomes in PKn subjects through the implementation of group discussion learning methods in students of class XII of the first semester of SMK Negeri 60 Jakarta in the 2015/2016 student year. The results obtained through data collection techniques, namely: observation, documentation tests and interviews, are: Learning outcomes cycle I is 75.6 while the results of Learning cycle II are 79.7. The conclusion of this study is